2007
DOI: 10.1007/s10811-007-9280-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid bioassays to evaluate the plant growth promoting activity of Ascophyllum nodosum (L.) Le Jol. using a model plant, Arabidopsis thaliana (L.) Heynh

Abstract: Ascophyllum nodosum extract products are used commercially in the form of liquid concentrate and soluble powder. These formulations are manufactured from seaweeds that are harvested from natural habitats with inherent environmental variability. The seaweeds by themselves are at different stages of their development life-cycle. Owing to these differences, there could be variability in chemical composition that could in turn affect product consistency and performance. Here, we have tested the applicability of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(119 citation statements)
references
References 20 publications
5
88
0
7
Order By: Relevance
“…Apart from the above organic and inorganic constituents, there is an evidence of existence of different other stimulatory and antibiotic substances. These findings are in agreement with Jeannin et al (1991), Vernieri et al (2005), Kowalski et al (1999), Zhang and Ervin (2008), Mancuso et al (2006), Norrie and Keathley (2006) and Rayorath et al (2008). Thus, being a wealthy source of versatile plant nutrients, phytohormones, amino acids, vitamins, stimulatory and antibiotic substances, the liquid sea weed extract enhances root volume and proliferation, bio-mass accumulation, plant growth, flowering, distribution of photosynthates from vegetative parts to the developing fruits and promotes fruit development, reduces chlorophyll degradation, disease occurrence etc.…”
Section: Discussionsupporting
confidence: 90%
“…Apart from the above organic and inorganic constituents, there is an evidence of existence of different other stimulatory and antibiotic substances. These findings are in agreement with Jeannin et al (1991), Vernieri et al (2005), Kowalski et al (1999), Zhang and Ervin (2008), Mancuso et al (2006), Norrie and Keathley (2006) and Rayorath et al (2008). Thus, being a wealthy source of versatile plant nutrients, phytohormones, amino acids, vitamins, stimulatory and antibiotic substances, the liquid sea weed extract enhances root volume and proliferation, bio-mass accumulation, plant growth, flowering, distribution of photosynthates from vegetative parts to the developing fruits and promotes fruit development, reduces chlorophyll degradation, disease occurrence etc.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have shown enhanced growth and yield in agricultural and horticultural crops such as wheat (Kumar and Sahoo 2011), winter rapeseed (Jannin et al 2013), apple (Malus domestica) (Basak 2008), strawberry (Alam et al 2013), tomato (Kumari et al 2011;Zodape et al 2011), spinach (Fan et al 2013), okra (Zodape et al 2008), olive (Olea europaea) (Chouliaras et al 2009), broccoli (Mattner et al 2013), and geranium (Pelargonium spp) (Krajnc et al 2012). Root and shoot growth of the model plant Arabidopsis was also enhanced by treatment with algal extracts (Rayorath et al 2008). Leaf chlorophyll content was increased following seaweed extract application in a number of studies (Blunden et al 1997;Mancuso et al 2006;Sivasankari et al 2006;Spinelli et al 2010;Fan et al 2013;Jannin et al 2013).…”
Section: Specific Effects Of Seaweed Extracts On Plantsmentioning
confidence: 97%
“…These extracts are reported to act as chelators, improving the utilization of mineral nutrients by plants and improving soil structure and aeration, which may stimulate root growth (Milton 1964). Seaweed extracts also act as biostimulants, enhancing seed germination and establishment, improving plant growth, yield, flower set and fruit production, increasing resistance to biotic and abiotic stresses, and improving postharvest shelf life (Mancuso et al 2006;Norrie and Keathley 2006;Hong et al 2007aHong et al , 2007bRayorath et al 2008;Khan et al 2009;Craigie 2011;Mattner et al 2013). The biostimulant effects often have been attributed to the presence of plant growth hormones and related low molecular weight compounds present in the extracts (Stirk and van Staden 1997;Tarakhovskaya et al 2007), but other research suggests that larger molecules including unique polysaccharides and polyphenols may also be important as biostimulants, as allelochemicals, and for enhancing resistance to stress (Klarzynski et al 2003;Zhang et al 2006;Rioux et al 2007;González et al 2013).…”
Section: Seaweed Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabela 1 -Efeito das doses (mL) do extrato de A. nodosum sobre o crescimento radicular diário (CR), em centímetros (cm), de plântulas do milho 'Impacto' em rizotrons , do primeiro (D1) ao décimo dia de avaliação ( , 1947;OLSEN et al, 1998) e, para tal, foi identificado que uma amilase independente da giberelina é induzida pelo extrato de A. nodosum (RAYORATH et al, 2008b).…”
Section: Resultsunclassified